Native Language Interference in EFL Students’ Writing of Reflective Journal in Indonesia - Anita, Anita; Silfani, Ani Nuraeni; Ulfah, Ulfah; Marzuki, Abdul Gafur; Viyani, Villy Al (Journal of English Education and Teaching, 2024)
Since writing is a competency that prepares students to complete all of their assignments and their thesis by the end of their university studies, learning it becomes imperative. This study aims to explore how L1 interference affects the language use, accuracy, and structure of reflective journals written by EFL students. It will also investigate the types of L1 interference that are most common in EFL students’ reflective journals and how these interferences affect their writing. The study also aims to provide insights into the challenges that EFL students face in writing reflective journals in English and identify effective strategies for addressing these challenges. This study was conducted by using qualitative approach with case study which is in descriptive. Results showed that Limited vocabulary is the most common sort of lexical and syntactical interference, followed in that sequence by word order, sentence structure, literal translation, verb tense and agreement, articles (a, an, and the), and false friends. Since limited vocabulary accounts for a sizable portion of interference cases 69 in total and it is the most prevalent kind. The main issue that pupils have is that they have trouble using the right words. This suggests that while expressing themselves in English, children frequently utilize phrases that might not be appropriate or have a restricted vocabulary.